TOXIC RELATIONSHIP IN ANNA TODD’S WATTPAD STORY AFTER - Rindiani Azzahra; Muhammad Fatih Suhadi (JOURNAL OF LANGUAGE, 2021)
This study is conducted to analyze the context of toxic relationships and find out the characteristics and negative impacts of toxic relationships in a story, After, written by Anna Todd, published in 2013. This study uses a descriptive qualitative method because the process of the results and discussion are accomplished descriptively. One of the significant theories used in this research is proposed by Glass (1995) who claims that toxic relationship is any relationship between people who do not support each other, there is conflict and one seeks to undermine the other, a competition, and   disrespect and a lack of cohesiveness. The characteristics of toxic relationships which are analyzed are excessive romantic jealousy, egoism (selfishness) of the partner, and lack of honesty. The negative impacts which are analyzed are disrespect and abuse. The results of this study are that toxic relationships are dangerous and should be avoided by a couple to get a harmony.